Physical Characteristics of Edible Film made from Carrageenan and Beeswax Composites through Nanoemulsion Process - Christmas Togas; Siegfried Berhimpon; Roike Iwan Montolalu; Henny Adeleida Dien; Feny Mentang (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
A research on producing edible film from composite of carrageenan and beeswax using nanoemulsionprocess has been conducted, with the objective is to analyze the effect of composite concentrationsand homogenization rate on physical characteristics of edible films. The edible films were made usingcarrageenan concentrations 3.5 and 4.5%, beeswax concentrations 0.2, 0.4, 0.6 and 0.8% and homogenizationrates of 2,000 and 3,000 rpm. Physical properties of the edible film were analyzed, i.e: thickness, tensilestrength, elongation, water vapor transmission rate and percent of solubility. The result, shows that thecomposite concentration ratio of carrageenan and beeswax and homogenization rate influence the physicalcharacteristics of edible film. Increased concentrations of composite and homogenization rates have highlysignificant effect (p<0.01) on decreased of water vapor transmission rate and increased of elongation andpercent of solubility, however have no significant effect (p>0.05) on increased of thickness and tensilestrength. The best treatment was obtained from composite concentration ratio of carrageenan 4,5% andbeeswax 0.8% with homogenization rate 3,000 rpm, with the average value of thickness 0.1534 mm, tensilestrength 22.44 N/mm2, elongation 22.5%, water vapor transmission rate 25.3411 g/m2/hr and percent ofsolubility 88%.